Are the implications of the financial growth cycle confirmed for Spanish SMEs? - Sánchez-Vidal, Javier; Martín-Ugedo, Juan Francisco (Journal of Business Economics and Management, 2012)
The aim of this paper is to analyze whether some of the empirical implications of the financial growth cycle hold in a sample of Spanish SMEs. We use a sample of 5,944 observations for the year 2007 and test several hypotheses using MANOVA analysis. The results show that companies tend to have different financing structures depending on their age and size. Hypotheses about trade credit, short term debt and risk are confirmed with respect to age, as the younger companies tend to use proportionally more trade credit and short term debt, and are riskier. Size is also associated in the expected way with trade credit, relative trade credit and relative short-term financial debt. On the other hand hypotheses about equity and the financing deficit are not confirmed. The effect of a pecking order behaviour over a long period of time may provide an explanation of why these two hypotheses are not confirmed.